Pemanfaatan Sistem Informasi Layanan Berbasis Digital Desa Sinarancang - Odi Nurdiawan; Ahmad Faqih; Ade Irma Purnamasari; Adisty Tri Putra; Kurniawan Fajar Abdulloh (CV. Multi Kreasi Media, 2023)
Utilization of Digital-Based Service Information Systems has become a major concern in efforts to improve service quality and progress in various rural areas. Sinarancang Village, as an example of a village facing various challenges in terms of access to information and services, has taken bold steps to adopt a digital-based information system as the main tool to overcome this problem. This Community Service explains how Sinarancang Village has integrated information technology into their services with the aim of increasing efficiency and accessibility. Community Service is an initiative that has been taken by the village government, community, and local partners in developing an inclusive information technology infrastructure. In addition, the success of Community Service has been achieved through the use of digital-based information systems in increasing access to health, education and village administration services. By combining a participatory approach and community education, Sinarancang Village has succeeded in creating an environment that supports the adaptation of information technology at the community level. The results of implementing this digital-based service information system show great potential for improving the quality of life of rural communities, promoting inclusivity, and encouraging economic growth in rural areas, one of which was initiated by the Anti Galau Sinarancang tourism village.